The Influence of Cartoon Films on Linguistic Growth in Early Childhood: A Psycholinguistic Study - Suryanti; Andi Agusniatih; Hafni Hafsah; Erdiyan Saputra; Ahmad Munawir (RETORIKA: Jurnal Ilmu Bahasa, 2024)
The cartoon Dora the Explorer is a work that combines bilingual elements, where Indonesian, English, and French are used simultaneously to support children's language learning. This study aims to examine the influence of cartoons on linguistic growth in children aged 2-6 years using a psycholinguistic approach. Psycholinguistics was used to study the development of children's linguistic growth after watching the cartoon Dora the Explorer, with a focus on the processes of language comprehension and production that occur within them. Cartoons often feature engaging visual elements and simple dialogue, making them an effective medium for introducing language to children. Through an analysis of the interaction between film content and children's cognitive development, the study explores how elements such as characters, stories, and phrase repetition can enhance speaking, listening, and linguistic understanding skills. Using observational methods and interviews, data were collected from children who regularly watch cartoons and their caregivers. The study indicates that Dora the Explorer encompasses various aspects of linguistic growth and social interaction. Additionally, results show that children exposed to cartoons acquire new vocabulary significantly faster and demonstrate improved communication abilities. These findings highlight the importance of selecting appropriate media to support early language learning processes and provide recommendations for parents and educators to utilize cartoons as effective learning tools.